Striking increase of natriuresis by low-dose spironolactone in congestive heart failure only in combination with ACE inhibition: mechanistic evidence to support RALES - Bauersachs, Johann; Fraccarollo, D.; Ertl, G.; Gretz, Norbert; Wehling, Martin; Christ, Michael (Circulation, 2000)
Background: A marked reduction of overall mortality in patients with severe congestive heart failure (CHF) has been demonstrated by addition of the mineralocorticoid receptor antagonist spironolactone to ACE inhibition. The aim of the present study was to examine a hypothesized interaction of spironolactone and ACE inhibitors in renal electrolyte and volume regulation. - - Methods and Results: Wistar rats with extensive myocardial infarction or sham operation were treated with either placebo, the ACE inhibitor trandolapril, low-dose spironolactone, or a combination of the 2. Twelve weeks after infarction, rats were housed in metabolic cages. Urinary volume and sodium excretion were significantly increased in CHF rats on a combined treatment with spironolactone and trandolapril (21.2±2.6 mL/d, 2489±320 mmol/d, mean±SD; P<0.05 versus other experimental groups) versus placebo-treated rats (16.7±5.6 mL/d, 1431±458 mmol/d),whereas these parameters were not affected in rats on either spironolactone (16.1±6.6 mL/d, 1153±273 mmol/d) or trandolapril alone (15.9±4.2 mL/d, 1392±294 mmol/d). The effects on natriuresis coincided with a significant reduction of left ventricular end-diastolic pressure (LVEDP) in rats on trandolapril and spironolactone (10.8±8.2 mm Hg; P<0.05 versus CHF placebo: 23.3±7.2 mm Hg; sham-operated rats: 5.1±0.9 mm Hg), whereas LVEDP remained elevated in rats treated with either compound alone. - - Conclusions: In the present study, we found an unexpected interaction of low-dose spironolactone and the ACE inhibitor trandolapril in experimental CHF leading to marked effects on renal electrolyte and volume regulation that were not apparent by treatment with either drug alone. These findings may explain the beneficial effects of spironolactone in CHF patients.
Gesehen am 28.06.2022